IMPLEMENTASI MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN PAI DAN BUDI PEKERTI PADA SISWA KELAS VIII D DI SMPN 1 POLANHARJO KLATEN TAHUN PELAJARAN 2025/2026 - Diah Novita Fardani; Siti Zubaidah Zahro Alifah Mubarokah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of Islamic Religious Education and Character Education (PAI and Character Education) learning still faces challenges, particularly the dominance of teacher-centered learning which limits students' active participation and critical thinking skills. This study aims to describe the implementation of the Problem Based Learning (PBL) model and identify the supporting and inhibiting factors in its application in PAI and Character Education learning at SMP Negeri 1 Polanharjo Klaten. This research employed a qualitative descriptive approach. Data were collected through observation, semi-structured interviews, and documentation involving Islamic Religious Education teachers, Grade VIII D students, and the vice principal for curriculum affairs. Data validity was ensured through source and method triangulation, while data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that the implementation of the PBL model was carried out through planning, implementation, and evaluation stages. The learning process involved presenting contextual problems, group discussions, problem-solving activities, presentations, and reflection, which encouraged students’ active participation. Supporting factors included students’ activeness and teachers’ ability to manage learning, while the main inhibiting factor was limited instructional time. Overall, the PBL model was effective in creating active, interactive, and student-centered learning experiences in PAI and Character Education classes.